2021
DOI: 10.1002/jcad.12368
|View full text |Cite
|
Sign up to set email alerts
|

Community‐Engaged Research and Evaluation in Counseling: Building Partnerships and Applying Program Evaluation

Abstract: Despite potential for rich engagement with community partners, community‐engaged research and evaluation are underutilized in professional counseling publications. This article includes an overview of principles for community‐engaged research and evaluation. Practical suggestions for developing community partnerships are outlined. A general guide for converging program evaluation within the context of community partnerships is provided, and considerations for navigating limitations of the approach are explored. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…This inclusion criterion was also aligned with the CSCORE Outcome Research Coding Protocol (Carey et al, 2008), for which one of the criteria is comparison groups. This inclusion criterion was beneficial in identifying intervention research, particularly due to the challenges of distinguishing intervention research and program evaluation in school counseling articles (Barrio Minton et al, 2021). Throughout the process, we thoroughly discussed any discrepancies and made final inclusion decisions as a whole team.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This inclusion criterion was also aligned with the CSCORE Outcome Research Coding Protocol (Carey et al, 2008), for which one of the criteria is comparison groups. This inclusion criterion was beneficial in identifying intervention research, particularly due to the challenges of distinguishing intervention research and program evaluation in school counseling articles (Barrio Minton et al, 2021). Throughout the process, we thoroughly discussed any discrepancies and made final inclusion decisions as a whole team.…”
Section: Methodsmentioning
confidence: 99%
“…While an increase in program evaluation initiatives by performed by school counseling scholars and practitioners is encouraging, it also potentially creates a lack of clarity in the types of intervention studies found in school counseling journals. Program evaluation is concerned with practical assessment and outcome reports based on the qualities of a certain context, whereas formal intervention research is interested in generalizability and theoretical conclusion (Barrio Minton et al, 2021; Dimmitt, 2009). Although theory is not necessarily completely absent from program evaluation procedures or the interventions they aim to describe, the mechanisms that contribute to specific school counseling outcomes might be unclear in program evaluation.…”
Section: The Use Of Theory In School Counseling Intervention Researchmentioning
confidence: 99%
“…However, many of the foundational participatory ideas parallel goals associated with feminist or narrative approaches that aim to deconstruct/reconstruct narratives related to oppression and identify personal plans for action. Additionally, researchers have shared examples for how counselors might apply participatory strategies for program evaluation (Barrio Minton et al., 2021) and in university–community‐partnered research (Hays et al., 2019). PAR frameworks and practices have also been used to develop group counseling interventions.…”
Section: An Application Of An Ecologically Informed Transdisciplinary...mentioning
confidence: 99%
“…Researchers have demonstrated the efficacy of university-school partnerships in various disciplines: teaching (Darling-Hammond et al, 2019;Jones et al, 2016), special education (Hoppey, 2016), play therapy (Taylor et al, 2022), school counseling (Bryan, 2005;Bryan et al, 2020) and mental health (Jenkins et al, 2023;Walter et al, 2019). However, researchers in counselor education have yet to explore partnership opportunities, despite calls within the profession (Barrio-Minton et al, 2021;Chen et al, 2023).…”
Section: University-school Partnershipsmentioning
confidence: 99%